1993
DOI: 10.1021/es00044a010
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxyl radical production from the gas-phase reactions of ozone with a series of alkenes under atmospheric conditions

Abstract: The gas-phase reactions of O3 with a series of alkenes have been investigated at 296 ± 2 K and atmospheric pressure of air in the presence of cyclohexane at concentrations sufficient to scavenge any OH radicals formed. The expected products of the OH radical-initiated reaction of cyclohexane, cyclohexanone and cyclohexanol, were observed in all cases. From a knowledge of the chemistry of cyclohexane in these reaction systems and the cyclohexanone and cyclohexanol formation yields obtained, the following format… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
297
3
3

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 291 publications
(334 citation statements)
references
References 23 publications
31
297
3
3
Order By: Relevance
“…As mentioned previously, the yield of OH employed to derive R OH from the O 3 -T2B calibration experiments has been inferred from scavenger studies (Atkinson and Aschmann, 1993;Fenske et al, 2000). These measured yields do not exhibit any pressure dependence, consistent with an OH production arising solely from the TCI decomposition.…”
Section: General Considerationsmentioning
confidence: 67%
“…As mentioned previously, the yield of OH employed to derive R OH from the O 3 -T2B calibration experiments has been inferred from scavenger studies (Atkinson and Aschmann, 1993;Fenske et al, 2000). These measured yields do not exhibit any pressure dependence, consistent with an OH production arising solely from the TCI decomposition.…”
Section: General Considerationsmentioning
confidence: 67%
“…Herein, the OH reached steady state concentrations of about 3×10 7 cm −3 , as described above. Ozonolysis alone did not induce new particle formation with detectable yields, although all SQT and a portion of the MT were consumed by ozone (including a contribution by dark OH arising from the ozonolysis of unsaturated VOC, since we did not use OH-scavengers, see Atkinson and Aschmann, 1993;Paulson et al, 1992Paulson et al, , 1998.…”
Section: Resultsmentioning
confidence: 99%
“…3), showed that winter concentrations of hydroxyl were about 50% of summer concentrations whereas scaling based upon ozone photolysis predicts concentrations only around 5% of summer concentrations. 8,9 This led to a realisation that other sources of hydroxyl are more important in the urban polluted atmosphere and these include photolysis of nitrous acid and formaldehyde as well as the decomposition of the Criegee biradical intermediate formed from ozone-alkene reactions 10 (see Box 1). Such processes are typically included in Chemistry-Transport Models (e.g., the RADM2 scheme 11 used in the WRF-Chem model), but depend critically upon reliable predictions of HONO and HCHO concentrations.…”
Section: Chemical Reaction Processes In the Urban Atmospherementioning
confidence: 99%